Access and use of secondary dental care of a large city of Rio Grande do Sul, Brazil - Caroline Schirmer; Alex Elias Lamas; Daniel Demétrio Faustino-Silva (Revista Sul-Brasileira de Odontologia, 2015)
The Brazilian Dental Specialty Centers (CEOs) were created due to a limitation of Brazilian public dental care. In 2004, the specialized services corresponded to no more than 3.5% of total dental clinical procedures. These services are a reference for oral health teams in primary care in order to perform additional procedures at this level of attention. Despite the expansion of specialized procedures, the resolution of these services is subject to discussion between managers and researchers. Objective: To evaluate the access and use of the secondary dental care of a large city. Material and methods: The descriptive retrospective longitudinal study was conducted using CEO primary data from November 2012 to July 2013. These data were obtained from the Technical Department of Oral Health and the coordination of services were analyzed and then compared to the guidelines of Ordinance no. #1.464/MS. Results: The performance of services was low, ranging from 47.2 to 60.6% of the overall fulfillment of goals, in average. By analyzing per subgroup, endodontics was the subgroup with lower fulfillment (33.2%) and periodontics was that with the most fulfillment (88.3%). Absenteeism on the first appointments, the average per service ranged between 29.4 and 44.2%, and periodontics was the most affected subgroup (51%). The percentage of finished treatment ranged from 52.9 to 66.4%, and stomatology was the subgroup with less number of finished treatments (19.2%). Conclusion: The study revealed low utilization of the evaluated services associated with high absenteeism. Further studies and management initiatives are necessary to find ways to optimize secondary dental care integration to primary care services.